Selective disclosures in the presence of uncertainty about information endowment - Pae, Suil (Journal of Accounting and Economics, 2005)
This paper analyzes a setting, where firms could have private information from various sources and disclose a selective subset of that information. Investors have uncertainty about how much information firms have. Using a stylized model where there are two signals about a firm's future value and the firm may be privately informed of none, one, or all of those signals, this paper establishes an equilibrium link between the cutoff value characterizing the partially informed firm's disclosure strategy and the partition of the signal space characterizing the fully informed firm's disclosure strategy. The paper also discusses potential extensions of the model.